دراسة نقدية للتفسير العلمي في العصر الحديث: A Critical Study of Contemporary Scientific Exegesis - Gampang Dadiyono; Achmad Abubakar; Muhammad Yusuf (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The significance of this research lies in its focus on contemporary scientific exegesis, which addresses the stance of modern scholars on this method of interpretation, particularly those who oppose it. The research aims to clarify doubts, provide accurate information to those who are confused on the matter, and present a clear, comprehensive, and accessible explanation, enabling thinkers to reflect and adopt the most appropriate stance—one that leans toward what is beneficial for them and others, and that is pleasing to the Lord of all worlds. The researcher uses inductive, analytical, and critical approaches. Among the findings are: the method of scientific exegesis must be approached with caution, and its steps should be carefully considered. The moderate view on this method is that it is permissible, but only when conditions are met to ensure that the interpretation is valid and acceptable. It is neither absolutely rejected nor accepted without reservations. Scientific exegesis should avoid excessive claims, and the apparent meaning of the text should not be diverted to another meaning unless absolutely necessary—such as when the literal meaning is impossible to accept.